Effectiveness of diabetes nursing course designed with hybrid learning pedagogy: A pilot study - ALPAR, ŞULE; OKUROĞLU, GÜLTEN (My University, 2022)
Objective: This study aimed to examine the effectiveness of hybrid learning pedagogy in a redesigned diabetes nursing course for senior nursing students in enhancing knowledge and skills related to diabetes education. Methods: A single-group pre-test and post-test quasi-experimental design were used. The study was conducted between January-June 2018 in a state university's nursing department in Istanbul, Turkey. Sixteen senior nursing students were included in the sample group of the study. Results: It was detected that the Insülin Injection Skill Checklist (II-SC) post-test score, Blood Glucose Measurement Skill Checklist (BGM-SC) post-test score, and Educational Skills Checklist (ESC) post-test score were significantly higher than the pre-test scores. There was a significant difference between the Mini Exams (ME) pre-test and post-test scores of participants for each online lesson. Conclusions: The study results showed that a hybrid learning-based diabetes nursing course effectively increases the knowledge and skills of students regarding diabetes education.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Tıbbi Ekoloji ve Hidroklimatoloji; Medicine; Health Sciences; Internal Medicine Sciences; Medical Ecology and Hydroclimatology; TIP, ARAŞTIRMA VE DENEYSEL; Klinik Tıp; Klinik Tıp (MED); MEDICINE, RESEARCH & EXPERIMENTAL; CLINICAL MEDICINE; Clinical Medicine (MED); Araştırma ve Teori; İncelemeler ve Referanslar (tıbbi); Research and Theory; Reviews and References (medical); Diabetes education; hybrid learning; nursing education; nursing student; KNOWLEDGE; NURSES; EDUCATION; STUDENTS; SKILLS